Analisis Peran Guru Kelas Anak Berkebutuhan Khusus Tipe Attention Deficit Hyperactivity Disorder (ADHD) dalam Pembelajaran Kelas 1 di SLB PGRI Kamal - Icha Berliana Putri Maharani; Nova Estu Harsiwi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the role of class teachers in dealing with special needs children with Attention Deficit Hyperactivity Disorder (ADHD) type in class 1 of SLB PGRI Kamal, Bangkalan, Madura. Using a descriptive qualitative approach with a case study method, data were obtained through interviews, observations, and documentation of class teachers who were the subjects of the study. The results show that teachers have a strategic role in supporting the learning of ADHD students through various responsive approaches, such as the use of visual media, dividing tasks into small parts, and reinforcing positive behavior. Teachers also make modifications in materials and assessments to accommodate individual student needs. In classroom management, teachers create an organized and conducive environment, and implement consistent routines to minimize distractions. Collaboration with parents and professionals is also an important aspect in supporting student development. However, teachers still face challenges, such as limited time, facilities, and lack of special training related to ADHD. This study emphasizes the importance of institutional support so that educational services for ADHD students can be more optimal and sustainable.